(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Dry cocoa bean quality is also determined by its microbe contamination level. Steaming process for dried cocoa beans as a pretreatment process was selected because of less effect on organic compound inside the dried cocoa bean. This experiment aim was to study microbial contamination level of cocoa beans using steaming process, determining its microbial population and evaluate its chemical changes. Experiment was carried out in Postharvest Laboratory of Indonesian Coffee and Cocoa Research Institute. Cocoa beans for the experiment were lots collected from four farms in Jayapura, Papua with different microbial contamination level for each lot. Results of this experiment showed that optimum steaming process was 15 minutes at 100 O C with 10 minutes preheating time. Microbial analysis result of the four lots after complete steaming process by total plate count method showed the same result (<3.0 x 103 cfu). Most of the decrease in microbial contaminant appeared in the plate was 73.5% of Staphylococcus aureusand 0.058% of Penicilliumsp. Bean acidity (pH) after steaming increased (4.76 to 4.80) and free fatty acid increased (1.81% to 1.96%) while carbohydrate content decreased (17.5% to 15.9%) and as well as protein content (12.6% into 11.7%). Key words: cocoa bean, steaming process, microbe reduction, nutrient changes